Relación de los anestésicos vasoconstrictores y los efectos adversos en pacientes que padecen de hipertensión arterial. Revisión bibliográfica - Suárez Suárez, Diana Raquel (2023)
Local anesthetics are pharmaceutical agents used daily in dentistry due to their vasoconstrictor components, which provide deep anesthesia, promote good hemostasis in the desired area, prevent toxic reactions, slow their absorption rate into the bloodstream, and induce ischemia in the operative area. However, they can also lead to complications in patients with cardiovascular diseases or hypertension. This issue becomes particularly relevant because there is a high prevalence of hypertensive patients worldwide seeking dental care. The use of local anesthetics may lead to changes in blood pressure values, making it challenging for the dentist to choose a safe anesthetic. Therefore, the present research aimed to determine the local anesthetic with a vasoconstrictor that causes the most significant alterations, its adverse effects, and its impact on hypertensive patients seeking dental care. This was achieved through an analysis of several articles published between 2013 and 2023, sourced from databases such as Pubmed-Medline, Google Scholar, Elsevier, and Scielo, which provided reliable information. The research revealed that mepivacaine with epinephrine in a concentration of 1:100,000 can lead to methemoglobinemia in hypertensive patients, making its use rare. The most recommended option is lidocaine with epinephrine at 1:800,000 because it produces immediate effects and returns to normal within minutes after the anesthetic takes effect. Therefore, it is demonstrated that the reactions caused by vasoconstrictors, such as changes in blood pressure, heart rate, pulse, and respiration, are related to the patient's overall health, anxiety, stress, or trauma experienced during previous dental treatments or examinations